Kontribusi Ekonomi Perempuan Penjual Ayam Goreng Gerobak di Beberapa Pasar Satelit di Kota Padang - Yuzaria, Dwi; Fitrini, Fitrini (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2010)
Increased  socio-economic  demands  has  elevated  the complexity  of  family  needs.  To fulfill all these needs, women  should  participate  in making  a  living.  This  study  aimed  to  look  at  the economic performance of women in small business, particularly in-cart-fried-chicken business; identify the constraints faced and provide an alternative to overcome the constraints. The study was conducted by  survey method with respondents  of  in-cart-fried-chicken  seller  on  some market  centers  in Padang city. The sample is determined by proportional allocation of 15 people, meanshile the data were analyzed using descriptive analysis method. The results of research is that the economic performance of women in this business is quite low with 5.07 working hours per day. Approximately 32.5% of all those business- women participate in all activities from planning to marketing. This business is potential enough to be developed, with an average  income  level of USD 92,259.58 per day and approximately 1.29 R/C  ratio. Internal  constraints  faced  by  these  women is the  pattern  of  relations  in  the  family  that marginalize women's role in meeting the economic needs of families, while the external constraint is the difficulty to seek  additional  capital  for  business development and fluctuations  in  the price of  chicken as main  raw material. An alternative that  can be offered  is to open a branch business at home  for women  to devote more time, and access to soft loans which apply an unheavy terms. The conclusion of the research was that  women  had  roles in  making  a  living  for  the  family,  however,  the  role  is  low  because there were patriarchi values as internal constraints and capital as the main external constraint. The solution  is to find for a soft loan and establish good relationships with suppliers of raw materials.